About the fascination of symmetry (KULT_online, 2016)
Walter Christaller developed his "Zentrale-Orte-Modell " in 1933 as part of his dissertation "Die zentralen Orte in Süddeutschland". This theory "understands cities and settlements as functional centers" (p.54; my translation) which provide certain economic functions within corresponding neighborhoods, while being divided by Christaller into hierarchically structured supply systems. In his latest historical study, Deutsche Raumplanung. Das Modell der "Zentralen Orte" zwischen NS-Staat und Bundesrepublik Karl R. Kegler traces the career of this model via its application and reception between the Nazi period and the first decades of Post-war Germany. Kegler carefully dissects Christaller’s theory, compares the concept of central places with other theories of contemporary spatial planners or geographers, and reflects upon its lines ofdevelopment. His conclusion questions the theoretical foundation of the established spatial planning in the German context.